2014
DOI: 10.1007/s12192-013-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil rich in eicosapentaenoic acid protects against oxidative stress-related renal dysfunction induced by TCDD in Wistar rats

Abstract: Humans are systemically exposed to persistent organic pollutants, of which 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) has become a major environmental concern. Exposure to TCDD results in a wide variety of adverse health effects which is mediated by oxidative stress through CYP1A1 activation and arachidonic acid metabolites. Eicosapentaenoic acid (EPA) exhibits antioxidant property and competes with arachidonic acid in membrane phospholipids and produces anti-inflammatory EPA derivatives. Since both EPA and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
2
9
1
Order By: Relevance
“…Additionally, both EPA and DHA protect against TCDD-induced oxidative stress and hepatic and renal injury in rats in vivo (Palaniswamy et al, 2014;Turkez et al, 2011a). Notably, however, in our study TCDD did not increase oxidative stress markers or increase fatty acid autooxidation products in the liver.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Additionally, both EPA and DHA protect against TCDD-induced oxidative stress and hepatic and renal injury in rats in vivo (Palaniswamy et al, 2014;Turkez et al, 2011a). Notably, however, in our study TCDD did not increase oxidative stress markers or increase fatty acid autooxidation products in the liver.…”
Section: Discussioncontrasting
confidence: 64%
“…Additionally, the n-3 PUFA diet significantly increases EPA and DHA, highly preferred endogenous fatty acid substrates for CYP1A1 (Arnold et al, 2010a,b), which could also reduce nonspecific CYP1A1 oxidation of other vascular fatty acid substrates. Others have reported that EPA reduces TCDD-induced CYP1A1 activity in vitro and in vivo (Palaniswamy et al, 2014(Palaniswamy et al, , 2015. The mechanism by which n-3 PUFAs reduce TCDDinduced CYP1A1 expression and activity is not known, although we did not observe a decrease in AHR expression in mice on the n-3 PUFAs diet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its anti-inflammatory activity, administration of EPA has been reported to suppress ROS generation in vivo (Richard et al, 2008 ; van den Elsen et al, 2013 ). EPA also possesses antioxidant activity in type 2 diabetic patients (Mahmoudabadi and Rahbar, 2014 ), in rats exposed to organic pollutants (Palaniswamy et al, 2014 ) and against oxidative stress in adipocytes (Kusunoki et al, 2013 ). Thus, our findings are in good agreement with the above previously reported observations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EPA has been shown to suppress inflammatory responses to stimuli other than CS in a number of animal models (Okabe et al, 2011 ; Jia et al, 2012 ; Poudyal et al, 2013 ; Schuster et al, 2014 ) and in various cell types (Moon et al, 2007 ; Mickleborough et al, 2009 ; Mullen et al, 2010 ; Wang et al, 2010 ; Jinno et al, 2011 ; Jung et al, 2012 ; Magee et al, 2012 ; van den Elsen et al, 2013 ). Furthermore, EPA has been reported to possess antioxidant activity when prescribed to treat patients (Mahmoudabadi and Rahbar, 2014 ) or when used as in vitro (Richard et al, 2008 ; Kusunoki et al, 2013 ; van den Elsen et al, 2013 ) or in vivo preparations (Okabe et al, 2011 ; Palaniswamy et al, 2014 ). Thus, the antioxidant and anti-inflammatory properties of EPA make it a potential drug for the treatment of CS-induced lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary supplementation with ALA (1%) was reported to counteract the toxic effect of a MeHg contaminated diet (5 mg/kg body weight) by restoring the antioxidant defences and reducing lipid peroxidation in liver, kidneys, brain, plasma and red blood cells of rats Ghosh, 2012a andGhosh, 2012b). The authors suggested that the protective effect of ALA might be due to its bioconversion into EPA, which is known for its antioxidant properties (through enhancing the cellular antioxidant defences) (Palaniswamy et al, 2014;Shakouri Mahmoudabadi and Rahbar, 2014). However, our results show that the biological importance of ALA is not only due to its bioconversion into valuable HUFAs.…”
Section: Discussionmentioning
confidence: 99%